Interleukin-1 Receptor-Associated Kinase 4 Deficiency in a Greek Teenager - Panagiota Karananou; Anastasia Alataki; Efimia Papadopoulou-Alataki (Case Reports in Immunology)
Background. Human interleukin- (IL-) 1 receptor-associated kinase 4 (IRAK-4) deficiency is a recently described primary immunodeficiency. It is a rare, autosomal recessive immunodeficiency that impairs toll/IL-1R immunity, except for the toll-like receptor (TLR) 3- and TLR4-interferon alpha (IFNA)/beta (IFNB) pathways. Case Report. We report the first patient in Greece with IRAK-4 deficiency. From the age of 8 months, she presented with recurrent infections of the upper and lower respiratory tract and skin abscesses. For this, she had been repeatedly hospitalized and treated empirically with intravenous antibiotics. No severe viral, mycobacterial, or fungal infections were noted. Her immunological laboratory evaluation revealed low serum IgA and restored in subsequent measurements; normal IgG, IgM, and IgE; and normal serum IgG subclasses. Peripheral blood immunophenotyping by flow cytometry and dihydrorhodamine (DHR) test revealed normal counts. She was able to make functional antibodies against vaccine antigens, including tetanus and diphtheria. She was administered with empirical IgG substitution for 5 years until the age of 12 years, and she has never experienced invasive bacterial infections so far. DNA analysis revealed a heterozygous variant in the patient: c.823delT (p.S275fs∗13 at protein level) in the IRAK4 gene. Conclusions. The importance of clinical suspicion is emphasized in order to confirm the diagnosis by IRAK4 gene sequencing and provide the appropriate treatment for this rare primary immunodeficiency, as soon as possible.